JEEViKA Multisectoral Convergence Initiative in Bihar: Engaging women’s groups to improve nutrition: Summary report - Gupta, Shivani; Kumar, Neha; Menon, Purnima; Pandey, Shinjini; Raghunathan, Kalyani (World Bank, 2019)
JEEViKA is a program by the Bihar Rural Livelihoods Promotion Society (part of the Department of Rural Development), with the support of the World Bank. It targets women in poor rural households, helping them improve their livelihoods and enhance household incomes through a core set of interventions: organizing the women into self-help groups (SHGs), training and strengthening the SHGs, federating the SHGs into village organizations (VOs) and cluster-level federations (CLFs), and establishing bank linkages for the SHGs and their federations. Over time, these groups can become membership-based social service providers, business entities, and valued clients of the formal banking system.